Vídeos tutoriais na educação a distância : as presenças do professor - Gama, Luciana de Assis (2012)
The dissertation Tutorial Videos in Distance Education: The Presence of the Teacher was developed for the master's degree in Education. The line of research is Education and Languages. This Masters program is part of the Graduate Education of the Federal University of Espirito Santo and was conducted from 2010 to 2011. This is a qualitative research, which outlines a methodological approach for virtual ethnography to contextualize the analytical corpus. It consists of seven video tutorials worked and tutoring in the disciplines of Bachelor's Degree in Visual Arts at the Center for Distance Education at UFES. They are: Color and Paint Lab, taught by Joyce Brandão teacher; Drawing I, given by Lincoln Guimaraes teacher and some videos produced by Julio Tiger mentor. The analysis of the videos is based on methodological discursive semiotics. The objective of this analysis is to understand through the joints in the content plan and expression plan how these teachers build their discourse and also how they are present in these videos. The research shows interviews with teachers and producers and also shows the video analysis. In some cases what is shown in interviews and what is shown in the video are in contradiction. Teachers may have the intention and proposal to do something but do not pass it on video. To get the analysis of selected videos, we walk a path that went through the audiovisual language, by use of video and contextualization of the Virtual Learning Environment in which these tutorial videos are hosted and are accessed during the course. With the assumption that the video is a strong didactic material to create closer ties between teachers and students in a distance education course, this thesis aims to contribute to analysis and creation of materials that have this purpose.